Stepwise Training for Reconstructive Microsurgery: The Journey to Becoming a Confident Microsurgeon in Singapore - Ramachandran, Savitha; Ong, Yee-Siang; Chin, Andrew YH; Song, In-Chin; Ogden, Bryan; Tan, Bien-Keem (Archives of Plastic Surgery, 2014)
Microsurgery training in Singapore began in 1980 with the opening of the Experimental Surgical Unit. Since then, the unit has continued to grow and have held microsurgical training courses biannually. The road to becoming a full-fledged reconstructive surgeon requires the mastering of both microvascular as well as flap raising techniques and requires time, patience and good training facilities. In Singapore, over the past 2 decades, we have had the opportunity to develop good training facilities and to refine our surgical education programmes in reconstructive microsurgery. In this article, we share our experience with training in reconstructive microsurgery.
Keywords: Microsurgery; Education; Reconstructive surgery